The Queen's Loyal 'Others' –the Metropolitan Jewish and Catholic Hierarchies, the Communal Press and the Diamond Jubilee of 1897. Issue 3 (1st September 2020) - Renshaw, Daniel
ABSTRACT: This article examines the Jewish and Catholic experience of acceptance, rejection and discrimination in late nineteenth-century Britain through the lens of the celebrations of Queen Victoria's Diamond Jubilee in the summer of 1897. Arguing that the Anglo-Jewish and English Catholic hierarchical discourses created at the time of the Jubilee reveal the continuing profound insecurities felt by the minority leaderships, the article will dissect the various 'stories' created around the events of the Jubilee, particularly in London. It will consider in turn how narratives were created stressing Victoria's personal role of liberator; how a premium was placed by the hierarchies on the different demographic strands of the minority communities behaving in aropriate 'English' class roles; and how this narrative was complicated – first by Irish nationalism and migrant Jewish radicalism, and secondly by the prejudices of the wider British establishment. Ultimately it will contend that the events of the Jubilee revealed a continued exclusion of Jewish and Catholic groups from the British ruling class, and that anti-Catholic sectarianism and antisemitism was not solely a matter of economic discrimination and physical violence against working-class communities, but also subtler forms of prejudice against more prosperous Jews and Catholics.